ANALYSIS OF TECHNICAL AND FINANCIAL ASPECTS OF THE CRAB TRAP FISHERY BUSINESS IN SALEMO ISLAND, NORTH LIUKANG TUPABIRING DISTRICT, PANGKEP REGENCY - Khusnul Khatimah Hasrun; Israwahyudi Israwahyudi; Muh. Ardiansyah (Jurnal Perikanan Unram, 2024)
Crab (Portunus pelagicus) is one of the economically important marine products produced from Indonesian coastal waters. Market demand for crab commodities continues to increase. Crab traps are a fishing tool that is very popular with fishermen for catching crab because this fishing tool is passive, cheap and easy to operate and selective for fish (environmentally friendly). Based on the above, bearing in mind the importance of efforts to improve the standard of living and welfare of fishermen, it is necessary to have a fishing business to make it more profitable and responsible. The aim of this research is to analyze the technical and financial aspects of the crab trap fishing business on Salemo Island in February and April 2018. This research uses a survey research method, with data collected using a questionnaire using a random sampling method for fishermen who operate crab traps. Based on the research results, technical aspects include the fishing ground for crab traps, which has muddy bottom topography. The fishing season in a year is the peak season in May–September, the normal season in March–April and the lean season in October–February. The production of catches by crab trap fishermen on Salemo Island, Pangkep Regency, ranges between 1.01 and 1.95 kg/trip/unit of fishing gear and 264 and 591 kg/year/unit of fishing gear. The average value of the R/C ratio for crab trap businesses is 1.26, so the crab trap business is feasible to develop.